Development of hydrogen sulfide donors for anti-atherosclerosis therapeutics research: Challenges and future priorities - Yang, Ye-Wei; Deng, Nian-Hua; Tian, Kai-Jiang; Liu, Lu-Shan; Wang, Zuo; Wei, Dang-Heng; Liu, Hui-Ting; Jiang, Zhi-Sheng (Frontiers in Cardiovascular Medicine, 2022)
Hydrogen sulfide (H2S), a gas transmitter found in eukaryotic organisms, plays an important role in several physiological processes. H2S is one of the three primary biological gas transmission signaling mediators along with nitric oxide, and carbon monoxide. Several animal and in vitro experiments have indicated that H2S can prevent coronary endothelial mesenchymal transition, reduce the expression of endothelial cell adhesion molecules, and stabilize intravascular plaques, suggesting its potential role in the treatment of atherosclerosis (AS). H2S donors are compounds that can release H2S under certain circumstances. Development of highly targeted H2S donors is a key imperative as these can allow for in-depth evaluation of the anti-atherosclerotic effects of exogenous H2S. More importantly, identification of an optimal H2S donor is critical for the creation of H2S anti-atherosclerotic prodrugs. In this review, we discuss a wide range of H2S donors with anti-AS potential along with their respective transport pathways and design-related limitations. We also discuss the utilization of nano-synthetic technologies to manufacture H2S donors. This innovative and effective design example sheds new light on the production of highly targeted H2S donors.